(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Researcher aims to find out: 1). To find out the Relationship between Height and Smash Ability in Volleyball Games on the Tindoli Village Women’s Volleyball Team?. 2). To find out the Relationship between Leg Muscle Explosive Power and Smash Ability in Volleyball Games on the Tindoli Village Women’s Volleyball Team?. 3). To find out the Relationship between Height and Leg Muscle Explosive Power and Smash Ability in Volleyball Games on the Tindoli Village Women’s Volleyball Team. The research method in this study is quantitative descriptive, with the sampling method being purposive sampling. The population in this study was members of the Tindoli Village Women’s Volleyball Team, totaling 15 people who were used as samples. The data analysis technique used was the product-moment correlation statistical technique. The results of the study showed that there was a Relationship between Height and Leg Muscle Explosive Power and Smash Ability in Volleyball Games on the Tindoli Village Women’s Volleyball Team. This is proven by the results of the calculation of the Product Moment correlation obtained by the results of this study showing Height to Smash Ability where rcount = 0.620 obtained rtable = 0.532 because rcount> rtable or 0.620> 0.532 with a significant level of 5% with a degree of difference (db) (N-1) = 15-1 = 14, and the results of the calculation of the Product Moment correlation of leg muscle explosive power to Smash Ability where rcount = 0.873 obtained rtable = 0.532 because rcount> rtable or 0.873> 0.532 with a significant level of 5% with a degree of difference (db) (N-1) = 15-4 = 14. Thus it is concluded that there is a significant relationship between Height and Leg Muscle Explosive Power to Smash Ability in Volleyball Games on the Tindoli Village women’s volleyball team.